Sosialisasi Manajemen Air Minum Di Kelurahan Pancoran Mas, Depok Dalam Mendukung Pembangunan Berkelanjutan - Dini Putri Saraswati; Shanti Darmastuti; Mansur Juned; Sophiana Widiastutie (CV. Multi Kreasi Media, 2025)
This community service activity aims to provide an understanding of drinking water management in Pancoran Mas Village, Depok, West Java through socialization activities. The problem is that many people still do not know how to maintain clean water sources that are drinkable. The method of community service is the implementation of a pre-test before socialization and a post-test after socialization to determine the level of community understanding. The results of community service found that the community knows how to maintain clean water sources so that they are drinkable. This community service has a positive impact on the development of good habits in maintaining environmental cleanliness to maintain clean water sources so that they are drinkable.